Sementes crioulas: autonomia, identidade e diversidade dos grupos camponeses em Orizona e Vianópolis - GO - Ribeiro, Welington Martins (2017)
The production of seeds, seedlings and creole breeds is actually present in the communities and peasant groups ensuring their social reproduction and permanence of the families in the field. It is through these varieties that traditional knowledge is passed between the generations, the food consumed by the families becomes safe and compatible with the socio-cultural reality of the region, the activities developed become more diversified and agrobiodiversity is preserved. This dissertation had as main objective to know the production of the creole varieties in the Taquaral and Santana Communities, in Orizona and Vianópolis, where were found six families producing creole seeds. Through local visits, participant observation and reports of peasants guardians interviewed, we can see that production places of the peasant groups have a great diversity of species if compared to the models of agricultural production adopted in that region and creole seeds contribute to this number of cultivated varieties. The identity and autonomy provided to their guardians of the creole seeds through their handling and use bring a sense of empowerment and uniqueness to the peasant groups and a possibility that it assists and recognized by society.